Immunosuppressed Miniswine as a Model for Testing Cell Therapy Success: Experience With Implants of Human Salivary Stem/Progenitor Cell Constructs - Wu, Danielle; Lombaert, Isabelle M. A.; DeLeon, Maximilien; Pradhan-Bhatt, Swati; Witt, Robert L; Harrington, Daniel Anton; Trombetta, Mark G; Passineau, Michael J; Farach-Carson, Mary C. (Frontiers in Molecular Biosciences, 2021)
An urgent need exists to develop large animal models for pre-clinical testing of new cell therapies designed to replace lost or damaged tissues. Patients receiving irradiation for treatment of head and neck cancers frequently develop xerostomia/dry mouth, a condition that could one day be treated by cell therapy to repopulate functional saliva-producing cells. Using immunosuppression protocols developed for patients receiving whole face transplants, we successfully used immunosuppressed miniswine as a suitable host animal to evaluate the long-term stability, biocompatibility and fate of matrix-modified hyaluronate (HA) hydrogel/bioscaffold materials containing encapsulated salivary human stem/progenitor cells (hS/PCs). Initial biocompatibility test was conducted in parotids of untreated miniswine. Subsequent experiments using hS/PC-laden hydrogels were performed in animals beginning an immunosuppression regimen on the day of surgery. Implant sites included the kidney capsule for viability testing and parotid gland for biointegration time periods up to eight weeks. No transplant rejection was seen in any animal assessed by analysis of the tissues near the site of the implants. First generation implants containing only cells-in-hydrogel proved difficult for handling in the surgical suite, and were modified to adhere to a porcine small intestinal submucosa (SIS) membrane for improved handling and could be delivered through the da Vinci Surgical System. Several different surgical techniques were assessed using the second generation 3D-salivary tissue (3D-ST) for ease and stability both on the kidney capsule and in the capsule-less parotid gland. For the kidney, sliding the implant under the capsule membrane and quick stitching proved superior to other methods. For the parotid gland, creation of a tissue “pocket” for placement and immediate multi-layer tissue closure was well tolerated with minimal tissue damage. Surgical clips were placed as fiduciary markers for tissue harvest. Some implant experiments were conducted with miniswine 90 days post-irradiation when salivation decreased significantly. Sufficient parotid tissue remained to allow implant placement and animals tolerated immunosuppression. In all experiments, viability of implanted hS/PCs was high with clear signs of both vascular and nervous system integration in the parotid implants. We thus conclude the immunosuppressed miniswine is a high value emerging model for testing human implants prior to first-in-human trials.